2018
DOI: 10.1111/peps.12268
|View full text |Cite
|
Sign up to set email alerts
|

Daily mistrust: A resource perspective and its implications for work and home

Abstract: Mistrust is a daily occurrence at work. Yet little is known about how perceptions of being mistrusted by coworkers may affect employees’ subsequent daily attitudes and behaviors. Indeed, the existing literature on mistrust has overwhelmingly focused on how mistrust affects the trustor (person whose trust is violated) but not the trustee (the mistrusted person). This is problematic because conservation of resources theory (COR) suggests that perceived mistrust is a negative experience likely to affect the mistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 150 publications
3
52
0
Order By: Relevance
“…Relatedly, although we supported several hypotheses in Study 1, our effect sizes were somewhat small (i.e., γ s = .06–.10). Although small effect sizes are somewhat common in ESM research (e.g., Baer, Matta, Kim, Welsh, & Garud, ; Lanaj et al., ; Zhou et al., ), and our variables explained meaningful incremental variance (i.e., 4–7%), it is reasonable to question the practical significance of our findings.…”
Section: Study 1 Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Relatedly, although we supported several hypotheses in Study 1, our effect sizes were somewhat small (i.e., γ s = .06–.10). Although small effect sizes are somewhat common in ESM research (e.g., Baer, Matta, Kim, Welsh, & Garud, ; Lanaj et al., ; Zhou et al., ), and our variables explained meaningful incremental variance (i.e., 4–7%), it is reasonable to question the practical significance of our findings.…”
Section: Study 1 Discussionmentioning
confidence: 68%
“…Indeed, Lanaj et al. () found that depleted employees enacted more passive deviant behaviors at work. Despite the low visibility of the behaviors we examined, depleted employees may still perceive potential costs associated with their enactment, and self‐regulate accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have observed that people have been raised to internalize their society's moral standards (Bandura, 1991), and that they are motivated to maintain the sense that, on the whole, they are good people (Bryan, Adams, & Monin, 2013;Mazar et al, 2008;Monin & Miller, 2001;Sherman & Cohen, 2002). Thus, violating moral principles can prove costly to the violator by threatening that sense of self-worth (Lanaj, Kim, Koopman, & Matta, 2018).…”
Section: The (Would Be) Hypocrite's Dilemmamentioning
confidence: 99%